Plains State University's naming rights dilemma - Popp, Nels; Eddy, Terry, active 2015; McEvoy, Chad D., 1971- (London : Human Kinetics, Inc., 2015)
In this case study, readers are placed in the role of a National Collegiate Athletics Association (NCAA) Division I Athletics Director and challenged to consider the issue of selling the corporate naming rights to the department's premier on-campus sports venue. Readers are exposed to a myriad of issues impacting such a decision and must weigh out such factors as: (a) the appropriateness of corporate commercialization in college athletics, (b) the pressure to balance a tight athletic department budget, (c) the impact of changing a facility name which holds significant nostalgic value to the fan base, (d) what type of sponsors might be an appropriate fit for a corporate naming rights sponsorship, and (e) what are the current trends among sport facility naming rights within college athletics. The case study is supported by many scholarly research citations but also includes important appendices, including a database of 44 current college athletic facility naming rights deals, populated with key variables. This database will assist readers in the difficult process of attempting to value naming rights for a fictional facility depicted in the case study.
Originally published in Popp, N., Eddy, T., & McEvoy, C. (2015). Plains State University's naming rights dilemma. Case Studies in Sport Management, 4(1), 14-20. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; National Collegiate Athletic Association; Sports administration